Cyber-related crime in South Africa: extent and perspectives of state’s roleplayers - Ezeji, Chiji L. (Acta criminologica, 2018)
This article examines cyber-related crime in South Africa and the efforts of the South African criminal justice system in combating its scourge. Cyber criminals make use of cyberattack techniques such as malicious software and viruses that attach themselves to normal files, consequently reproducing themselves to cause damage to a computer system, or network. Other techniques such as Worms, Trojan and Backdoor programs are also used to gain access to a computer system, or network. Viruses and malicious software can also be transported by cyber criminals. Other related cybercrimes in South Africa such as e-commerce fraud and identity theft, involves the use of email, or web pages, to convince victims to reveal their personal or financial information. These have increased. Stolen information is used by cyber criminals to further other crimes. Furthermore, online credit cards fraud has increased, and cyber bulling are witnessed in different schools in South Africa. A qualitative research approach, through in-depth interviews was adopted for this study, and twelve persons participated through purposive sampling. Findings from this study indicate (among others) that there is a shortage of criminal justice experts who are knowledgeable about cyber-related cases. In addition, the study found that legislation on cyber-related crime in South Africa are not sufficient enough to deter cyber criminals from venturing into the act. The study also found that while individual victims often fail to report the crime due to ignorance, organisations often forgo reporting cybercrimes in a bid to protect their reputation. The study makes recommendations from the findings.